Comparative Efficacy of Danshen Class Injections for Treating Acute Coronary Syndrome: A Multidimensional Bayesian Network Meta-Analysis of Randomized Controlled Trials - Guo, Siyu; Wu, Jiarui; Ni, Mengwei; Jia, Shanshan; Zhang, Jingyuan; Zhou, Wei; Liu, Xinkui; Wang, Miaomiao; Zhang, Xiaomeng (Frontiers in Pharmacology, 2020)
Background: Acute coronary syndrome, that is a common and serious cardiovascular disease, imposes a huge economic burden on global public health. And Danshen class injections are commonly used in the treatment of acute coronary syndrome in China. Thus, the Bayesian network meta-analysis was devised to investigate the efficacy of different Danshen class injections against acute coronary syndrome. Methods: Eligible inclusion and exclusion criteria were established in advance. Then, a systematic literature search was performed in several databases from inception to February 2020. Further, the included randomized controlled trials data were adopted to calculation, prepare graphs and multidimensional cluster analysis by WinBUGS 1.4.3, Stata V.13.0 and R 3.6.1 software, respectively. Results: A total of 53 eligible randomized controlled trial studies with 6401 patients were obtained that evaluated the clinical effectiveness rate, the level of hypersensitive C-reactive protein, C-reactive protein, interleukin-6, fibrinogen and adverse reactions after the application of Danshen class injections plus western medicine. Compared with western medicine alone, Danshen class injections combined with western medicine therapy were associated with significantly improved the therapeutic effect. In addition, the results of the multidimensional cluster analysis demonstrated that Danhong injection + western medicine and Danshen injection + western medicine had better therapeutic effects. However, since most eligible randomized controlled trial studies did not focus on the monitoring of adverse reactions, the safety of these Chinese herbal injections needs to be further explored. Conclusion: Based on this Bayesian network meta-analysis results, Danhong injection + western medicine and Danshen injection + western medicine might have a better impact on acute coronary syndrome patients. Nevertheless, more large samples, high-quality clinical and multicenter randomized controlled trial studies should be tested and verified in the future.